The Role of Foster Parents in Shaping Children's Social Interactions at the Bojongsoang Orphanage in Bandung - Sopiani, Latifah; Komala, Vivi Patra; Karyamah, Imas (Journal of Islamic Early Childhood Education (JOIECE): PIAUD-Ku, 2025)
This study examines the role of foster parents in shaping the social interactions of children living in the Indonesian Orphanage Foundation (PYI) Bojongsoang, Bandung. The background of the study lies in the social adaptation challenges experienced by children upon entering the orphanage environment. The objectives of the study are to (1) describe the characteristics of children’s social interactions in the orphanage, and (2) analyze the role of foster parents in the process of developing these social interactions. The research employed a descriptive qualitative method with a phenomenological approach. Data was collected through participatory observation, semi-structured interviews with three foster parents and seven foster children, as well as documentation of daily orphanage activities. Data analysis followed the reduction–display–verification cycle (Miles, Huberman & Saldaña). The main findings include: (1) new children’s social interactions initially tend to be passive, isolated, and influenced by habits formed prior to entering the orphanage; (2) foster parents implemented several strategies, namely (a) ritual modeling (joint religious practices), (b) habituation through daily tasks (promoting independence), and (c) providing guidance and emotional reinforcement; (3) the combination of these strategies effectively increased children’s social interaction frequency, self-confidence, and cooperative skills, although the adaptation process requires time and individualized approaches. The study concludes that the role of foster parents is significant in facilitating children’s social transitions within the orphanage. Practical recommendations include the development of adaptation-orientation programs, parent training for foster parents, and further research using a mixed-methods approach.